Dynamic delivery analysis of adsorptive natural gas storages at room temperature - Ridha, Firas Noori; Yunus, Rosli M.; Rashid, Mohd.; Ismail, Ahmad Fauzi (Elsevier B.V., 2007)

(untitled)
This work analyzes the performance of adsorptive natural gas (ANG) storage during dynamic discharge phase at room temperature. Various aspects of the dynamic system were studied, however, emphasis was given to the delivery capacity of the storage cylinder since it is the absolute measure of ANG storage system viability. The results demonstrated that activated carbons have better delivery capacities than molecular sieve zeolite and silica gel in spite of their higher thermal instability. Dynamic delivery capacities were found to be related inversely to discharge rate as a subsequent of further thermal instability. Increase in discharge rate from 1 L min− 1 to 5 L min− 1 resulted in the severest reduction in steady state delivery capacity, represented by a net factor between 7.6 and 12.1% taking the total delivery capacity as a reference. This range is dependent on the adsorbent type and properties. However, no hydrodynamic hindrances were observed in spite of these adsorbents were in powder form. Non-methane hydrocarbon gases have potential impacts on all types of delivery capacities within a reduction factor of 19.4% for natural gas containing 14.98 and 14.54 vol.% of ethane and propane discharged at 1 L min− 1. Such behavior appears to be mainly governed by the deactivation degree of the adsorbent with heavier hydrocarbon molecules